The Effect of Different Intensities of Acute Aerobic Exercise on Plasma Resistin Concentration and Insulin Resistance Index in Type 2 Diabetic Males - Ziba Davoudi; Mohsen Ghanbarzadeh; Saeid Shakeriyan; Abdolhamid Habbibi (Fasa University of Medical Sciences, 2016)
Background & Objectives: Today, the increase in diabetes all over the world and positive results of locomotor activity and exercise on factors related to this disease have been taken into consideration. The aim of this study is to investigate the effect of different intensities of acute aerobic exercise on plasma resistin levels in men with type II diabetes. Materials & Methods: The psent study is a quasi-experimental one. Ten subjects with Type II diabetes after at least 10 hours of fasting in a crossover design with three levels of 40%, 60%, and 80% VO2max ran on a treadmill for three sessions. Blood samples were measured before, immediately after, and 24 hours after any severity. Two-way analysis of variance with repeated measures and Pearson correlation test were used to analyze the data. Results: The findings showed that resistin levels, glucose, insulin, and insulin resistance index (HOMA-IR) immediately after and 24 hours after the three intensities of acute aerobic exercise were not significantly different, as compared to exercise trials before There is no substantial difference between resistin, glucose, insulin, and HOMA-IR immediately after and 24 hours after the acute aerobic exercise at different intensities (p>0.05). There is also no noticeable relationship between resistin, glucose Conclusion: It can be stated that acute exercise with different intensities does not affect resistin action in individuals with diabetes. These results may be due to the constant energy cost which is equivalent to 300 kcal per session, having no influence on the study variables.